Unlocking physiological transformations in riverine buffaloes following uterine torsion correction - YADAV, RISHIPAL; SINGH, GYAN; YADAV, POOJA (The Indian Journal of Animal Sciences, 2023)
This study aimed to examine the physiological alterations in riverine buffaloes with incompletely dilated cervix after the uterine torsion correction and the main objective was to understand the hormonal changes that lead to complete cervical dilatation following detorsion, facilitating per-vaginal birth. Torsion characteristics in buffaloes (n=24) were examined, and detorsion was performed using Sharma’s Modified Schaffer’s approach. Blood samples were collected pre-detorsion, post-detorsion, and at parturition. The average cervical dilation rate was 1.22±0.16 cm/h, and detorsion-to-parturition duration averaged 17.38±1.44 h. There were no significant differences between haematological and biochemical parameters at three-time intervals except serum calcium. Progesterone levelsdecreased progressively (1.43±0.01 ng/mL, 1.37±0.01 ng/mL, 1.34±0.01 ng/mL), while estradiol levels increased significantly (65.86±2.05 pg/mL, 77.08±2.05 pg/mL, 91.8±2.55 pg/mL) from pre-detorsion to post-detorsion and parturition. The levels of cortisol were significantly higher pre-detorsion (24.3±2.07 ng/mL) and post-detorsion (27.1±2.5 ng/mL) than at parturition (18.31±1.76 ng/mL). In conclusion, elevated estradiol levels, coupled with reduced progesterone, post-detorsion, trigger complete cervical dilatation, facilitating per-vaginal birth. This study sheds light on the hormonal dynamics driving the birthing process in buffaloes after uterine torsion correction.